(untitled) (Journal of University of Babylon for Engineering Sciences, 2020)
The present paper focuses on the study of the mechanical properties of PMMA used in the preparation of dental molds has many problems. The purpose of this work is to eliminate as much as possible. Most of the problems caused by using polyethyl metha acrylate alone are the addition of titanium granules of different sizes. In act out to end a passable and identical direction of Ti sods in the polymer influence, mixer milling process was applied. The study is conducted in the preparation of samples of PMMA with micronized titanium granules at( 0%, 0.5%, 1% , 1.5%), and other specimens of polymer are reinforced with titanium nanoparticles and in the same proportions. The tests are carried out to determine the validity of the composite material for use, the results are obtained from the tests of impact,and tensile testing where the specimens are reinforced with nanoparticles whose mechanical properties are (6 J/mm2,5.5MPa) the highest percentage of titanium nanoparticles, Corrosion rate decreased from(0.677 to 0.0015) a percentage (14.77% ) ie give the highest and best results.